Nano-radiopharmaceuticals as therapeutic agents - Dixit, Tanu; Dave, Nayomi; Basu, Kausani; Sonawane, Pranav; Gawas, Trutuja; Ravindran, Selvan (Frontiers in Medicine, 2024)
In recent years, there has been an increased interest in exploring the potential synergy between nanotechnology and nuclear medicine. The application of radioactive isotopes, commonly referred to as radiopharmaceuticals, is recognized in nuclear medicine for diagnosing and treating various diseases. Unlike conventional pharmaceutical agents, radiopharmaceuticals are designed to work without any pharmacological impact on the body. Nevertheless, the radiation dosage employed in radiopharmaceuticals is often sufficiently high to elicit adverse effects associated with radiation exposure. Exploiting their capacity for selective accumulation on specific organ targets, radiopharmaceuticals have utility in treating diverse disorders. The incorporation of nanosystems may additionally augment the targeting capability of radiopharmaceuticals, leveraging their distinct pharmacokinetic characteristics. Conversely, radionuclides could be used in research to assess nanosystems pharmacologically. However, more investigation is needed to verify the safety and effectiveness of radiopharmaceutical applications mediated by nanosystems. The use of nano-radiopharmaceuticals as therapeutic agents to treat various illnesses and disorders is majorly covered in this review. The targeted approach to cancer therapy and various types of nanotools for nano-radiopharmaceutical delivery, is also covered in this article.